Herbal Therapies in Functional Gastrointestinal Disorders: A Narrative Review and Clinical Implication - Kim, Yong Sung; Kim, Jung-Wook; Ha, Na-Yeon; Kim, Jinsung; Ryu, Han Seung (Frontiers in Psychiatry, 2020)
The pathophysiology of functional gastrointestinal disorders (FGIDs) is still unclear and various complex mechanisms have been suggested to be involved. In many cases, improvement of symptoms and quality of life (QoL) in patients with FGIDs is difficult to achieve with the single-targeted treatments alone and clinical application of these treatments can be challenging owing to the side effects. Herbal preparations as complementary and alternative medicine can control multiple treatment targets of FGIDs simultaneously and relatively safely. To date, many herbal ingredients and combination preparations have been proposed across different countries and together with a variety of traditional medicine. Among the herbal therapies that are comparatively considered to have an evidence base are iberogast (STW-5) and peppermint oil, which have been mainly studied and used in Europe, and rikkunshito and motilitone (DA-9701), which are extracted from natural substances in traditional medicine, are the focus of this review. These herbal medications have multi-target pharmacology similar to the etiology of FGIDs, such as altered intestinal sensory and motor function, inflammation, neurohormonal abnormality, and have displayed comparable efficacy and safety in controlled trials. To achieve the treatment goal of refractory FGIDs, extensive and high quality studies on the pharmacological mechanisms and clinical effects of these herbal medications as well as efforts to develop new promising herbal compounds are required.